POLIGAMI DALAM PERSPEKTIF SYADZ AD-DZARI’AH - Misbachul Fitri, Abdul Basit (USRATUNA: Jurnal Hukum Keluarga Islam, 2020)
In this study we try to describe polygamy in the perspective of Syadz adz-Dzari'ah, namely prevention, because it is feared that there will be conflicts within the family, between wives and husbands, between other wives, and between children. This research is a comparative literature study, the study material comes from literature sources. The technique of collecting data is by means of observation data collection (organizing data). Second, through library research. namely seeing, observing, seeking. The approach uses qualitative. The data were then collected and analysis techniques were carried out. The results of the data analysis were written in descriptive form. Data analysis used the content analysis stage, comparative analysis (content analysis and differentiating analysis). analyzing polygamy in the perspective of Syad ad-Dzari'ah. Polygamy when it causes ongoing conflicts and is unable to provide legal solutions, it is better to avoid it because when conflicts and disputes occur, the household will not be realized as sakinah mawaddah wa rahmah and barakah families. Even though marriage aims to find happiness, tranquility, blessings and all one's actions after marriage have the value of worship.